Changes in skin surface temperature after a 10-minute warm-up on a bike ergometer - Fröhlich, M.; Ludwig, O.; Zeller, P.; Felder, H. (International Journal of Kinesiology & Sports Science, 2015)
Introduction: Infrared thermography (IRT) is a non-invasive, non-contact procedure for skin surface temperature (SST) diagnostics and represents an effective, safe, and relatively cost-effective diagnosis tool for estimating the SST. While IRT has been established as a diagnosis tool in numerous medical areas of application, it is still in its initial stages as regards to sports science. We will therefore examine the extent to which IRT can be used for diagnosing the SST after a 10-minute warm-up phase. Method: 20 male sports students (23.0 ± 1.6 years; 75.8 ± 9.0 kg; 181.0 ± 6.8 cm) participated in this study. After a standardized preparation phase, the SST of the lower and upper extremities as well as the trunk was determined in a resting state. This was followed by a 10-minute warm-up phase on a bike ergometer set to 1.5 W/kg body weight and a cadence of 60-80 rpm. After the warm-up, the SST was determined again for the 1st to 10th minute of the post-strain phase. Results: The 10-minute warm-up resulted in a significant change in the SST over the time of measurement (P < 0.05; Eta2 = 0.16). Furthermore, a significant difference of the SST among the different areas of the body was identified (P < 0.05; ?2p = 0.15). The interaction between the time and the area of measurement was also significant (P < 0.05; Eta2p = 0.16). The drop in SST from resting state to the first measurement after the 10-minute warm-up phase was 1.16°C and 3.7% in the trunk musculature. The temperature of the arm musculature dropped by 0.59°C (1.9%), while the temperature of the leg musculature decreased by 1.12°C (3.6%). Ten minutes after the warm-up, the SST of legs and arms was back at the initial state before the strain, but the trunk SST was still 0.74°C (2.3%) lower. Discussion: IRT shows a characteristic SST progression after muscular warm-up. Different SSTs occur depending on the body area, which needs to be considered for standardized warm-ups on the bike ergometer. Changes in skin surface temperature after a 10-minute warm-up on a bike ergometer.